Growth curves of Nile tilapia (Oreochromis niloticus) strains cultivated at different temperatures - doi: 10.4025/actascianimsci.v35i3.19443 - Vander Bruno Santos; Edson Assunção Mareco; Maeli Dal Pai Silva (Acta Scientiarum. Animal Sciences, 2013)
Growth of Red, GIFT and Supreme Nile tilapia strains were evaluated. Fish were cultivatedin indoor recirculation systems in 0.5 m³ tanks with controlled temperatures of 22, 28 and 30°C. Randomsamples of 20 fish from each strain (10 fish tank-1) were weighed at day 7, 30, 60, 90 and 120. Exponentialmodel (y=AeKx) and Gompertz model (y = Aexp(-Be-Kx)) were fitted and the estimates parameters wereobtained by Weighted Least Squares. At 22°C, Red, GIFT and Supreme strain presented similar growthand fit of exponential model. GIFT and Supreme strain presented higher growth rate at 30°C of cultivationwhen compared to Red strain. Temperature influences weight and age at the inflection point. Thetemperature of cultivation influences the growth description of Red, GIFT and Supreme tilapia strains. Itchanges the age and weight at inflection point and the qualities of growth model fits, changing the variationof the batch.